Connections between the matching and chromatic polynomials - E. J. Farrell; Earl Glen Whitehead (International Journal of Mathematics and Mathematical Sciences)
The main results established are (i) a connection between the matching and chromatic polynomials and (ii) a formula for the matching polynomial of a general complement of a subgraph of a graph. Some deductions on matching and chromatic equivalence and uniqueness are made.